Magnetic‐based photosensitizer to improve the efficiency of antimicrobial photodynamic therapy against mature dental caries‐related biofilms - Abdulrahman A. Balhaddad; Lamia Mokeem; Rashed Alsahafi; Michael D. Weir; Hockin H. K. Xu; Mary Anne S. Melo (MedComm – Biomaterials and Applications, 2023)
Abstract Antimicrobial photodynamic therapy (aPDT) shows promise in eliminating oral pathogens without inducing microbial resistance. Yet, it faces limited biofilm penetration by the photosensitizer, which hinders its efficacy against mature, thick biofilms. This study assesses the effectiveness of the MagTBO (magnetic nanoparticles and toluidine‐blue ortho) nanoplatform against mature Streptococcus mutans biofilms associated with dental caries. The study employs constant‐depth film fermenter (CDFF) models, known as “artificial mouth,” to replicate caries processes and allow biofilm growth over teeth. This method enables the evaluation of biofilm‐induced mineral loss under cariogenic challenge over 5 and 10 days. The study shows that MagTBO improves aPDT's effectiveness against highly mature and complex biofilms over 5 and 10 days. However, the biofilm reduction unaffected the mineral content in the underlying dentin. This presents a promising approach for clinical aPDT protocols. However, it is crucial to acknowledge that these findings are based on in vitro studies and may necessitate further clinical confirmation. In summary, our data indicate that magnetic‐based photosensitizers enhance the modulation of pathogenic oral biofilms by aPDT, offering potential advancements in clinical aPDT protocols.